Kingdom of the Netherlands-Netherlands : Financial Sector Assessment Program:: Technical Note-Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for the Netherlands on banking supervision. The financial resilience of banks in the Netherlands has been strengthened in recent years, and banks are benefiting from continuing economic recovery. Broad-based economic recovery is helping stimulate demand for credit, although credit growth remains slow and unemployment continues to fall. Housing markets have started to recover since 2013 with prices and transaction volumes picking up. There has been an improvement in the financial position of Dutch banks. Cost efficiency has improved, and profitability has recovered. The banks migration to the new Basel III standards is also well underway for capital adequacy and liquidity.